DIPG-55. PATTERNS OF CEREBROSPINAL FLUID DIVERSION AND SURVIVAL IN CHILDREN WITH DIFFUSE INTRINSIC PONTINE GLIOMA: A REPORT FROM THE INTERNATIONAL DIPG REGISTRY. (4th December 2020) - Cooney, Tabitha; DeWire-Schottmiller, Mariko; Lane, Adam; Saab, Raya; Bandopadhayay, Pratiti; Dorris, Kathleen; Packer, Roger; Kilburn, Lindsey; Minturn, Jane; Dodgshun, Andrew; Parkin, Sara; Goldman, Stewart; et al.
Abstract: There is no standard of care for cerebrospinal (CSF) diversion in children with diffuse intrinsic pontine glioma (DIPG), nor understanding of survival impact. We evaluated CSF diversion characteristics in children with DIPG to determine incidence, indications and potential impact on survival. Data was extracted from subjects registered in the International DIPG registry (IDIPGR). IDIPGR team personnel obtained clinical and radiographic data from the registry database and when appropriate, abstracted additional data from individual medical records. Univariable analyses were performed using the Fisher's exact test or Wilcoxon rank sum test. Survival was estimated using the Kaplan-Meier method. Evaluable patients (n=457) met criteria for DIPG diagnosis by central radiology review. Ninety-two patients (20%) had permanent CSF diversion. Indications for permanent diversion were hydrocephalus (41%), hydrocephalus and clinical symptoms (35%), and clinical symptoms alone (3%). Those with permanent diversion were significantly younger at diagnosis than those without diversion (median 5.3 years vs 6.9 years, p=0.0002), otherwise no significant differences in gender, race, or treatment were found. The progression-free and overall survival of those with permanent CSF diversion compared to those without permanent diversion was 4.5 and 10.9 months vs 6.9 and 11.2 months, respectively (p=0.001, p= 0.4). There was no significant difference in overall survival in patients with or without permanent CSF diversion among a large cohort of DIPG patients. Patients without permanent diversion had significantly prolonged progression free survival compared to those with permanent diversion. The qualitative risks and benefits of permanent CSF diversion need to be further evaluated.